2016
DOI: 10.1002/cssc.201600101
|View full text |Cite
|
Sign up to set email alerts
|

Kagóme Cobalt(II)‐Organic Layers as Robust Scaffolds for Highly Efficient Photocatalytic Oxygen Evolution

Abstract: Two Kagóme cobalt(II)-organic layers of [Co3 (μ3 -OH)2 (bdc)2 ]n (1) and [Co3 (μ3 -OH)2 (chdc)2 ]n (2) (bdc=o-benzenedicarboxylate and chdc=1,2-cyclohexanedicarboxylate) that bear bridging OH(-) ligands were explored as water oxidation catalysts (WOCs) for photocatalytic O2 production. The activities of 1 and 2 towards H2 O oxidation were assessed by monitoring the in situ O2 concentration versus time in the reaction medium by utilizing a Clark-type oxygen electrode under photochemical conditions. The oxygen e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 100 publications
0
7
0
Order By: Relevance
“…By far, most reported photocatalysts for water oxidation are active at high pH, but may be deactivated in acid solution . Some are even lost the photocatalytic capacity in neutral pH range . Nakamura et.…”
Section: Resultsmentioning
confidence: 99%
“…By far, most reported photocatalysts for water oxidation are active at high pH, but may be deactivated in acid solution . Some are even lost the photocatalytic capacity in neutral pH range . Nakamura et.…”
Section: Resultsmentioning
confidence: 99%
“…In the as-synthesized structure, ultrathin CoO nanowires are confined in continuous ultrathin graphitic carbon and assemble preferentially into 3D arrays. [22] Briefly, Co(NO 3 ) 2 ·6H 2 O with equimolar o-benzenedicarboxylate acid was fed into CH 3 OH-H 2 O to form a transparent solution at room temperature under magnetic stirring ( Figure 1A). Additionally, the open space between neighboring nanowires not only allows for easy permeation of the electrolyte but also alleviates the volume change upon Li + insertion/extraction.…”
mentioning
confidence: 99%
“…Specifically, the 2D Kagóme MOL precursor was first synthesized by a typical solvothermal method. According to our previously reported procedure, its structure was found via X‐ray single‐crystal diffraction to be formulated by [Co 3 ( µ ‐OH) 2 ( o ‐benzenedicarboxylate) 2 ] n (Figure A–C) . Briefly, Co(NO 3 ) 2 ·6H 2 O with equimolar o ‐benzenedicarboxylate acid was fed into CH 3 OH‐H 2 O to form a transparent solution at room temperature under magnetic stirring (Figure A).…”
mentioning
confidence: 99%
“…A comparative study using reported materials with similar instrumental set ups is tabulated in Table 3. 25,60–65 The present CLSR material is superior compared with many reported mixed metal oxides as well as polyoxometalates. Though the amount of the catalysts is varied in materials, the trend of our results for oxygen evaluation is really encouraging in the similar class of materials.…”
Section: Resultsmentioning
confidence: 84%